Mobile Payment Service Adoption: Understanding OVO E-Wallet Customers among GEN Y and GEN Z in Bandung, West Java - Viony, Regya; Widodo, Arry (Journal of Indonesia Marketing Association (IMA), 2024)
This study aimed to determine the factors that influence the Y and Z generation consumers in using OVO E-wallet in the city of Bandung. The analysis employed the Unified Theory of Acceptance and Use of Technology (UTAUT) model, namely performance expectancy (PE), social influence (SI), and behavioral intention (BI). The data analysis was carried out using the structural equation model (SEM-PLS) on the final data collected as many as 400 respondents. The obtained results indicated that the performance expectancy (PE) and social influence (SI) have a positive and significant effect on the behavioral intention (BI) regarding the use of OVO mobile payment. In addition, the social influence (SI) moderates the performance expectancy (PE) towards the behavioral intention (BI). Generations Y and Z have high awareness and strong enthusiasm for adopting OVO mobile payment as long as it provides benefits. One strategy to encourage the adoption of OVO mobile payments among the Y and Z generations is to facilitate financial transactions in an expeditious manner. The social influence (SI) is also a factor regarding the adoption of OVO mobile payments. This suggests that generations Y and Z rely more on advice and recommendations from important people (such as family, friends and relatives) in the adoption of OVO mobile wallet.